Incidence and risk factors of kidney allograft loss due to BK nephropathy in the pediatric population: A retrospective analysis of the UNOS/OPTN database. (27th November 2020) - Patel, Het; Rodig, Nancy; Agrawal, Nikhil; Cardarelli, Francesca
Abstract: Background: BK virus infection can lead to graft dysfunction and loss in kidney transplant recipients. Risk factors for BKV and BKVN have been inadequately studied in children. Here, we evaluate the incidence and risk factors of allograft loss due to BKVN in the pediatric population of the UNOS data set. Methods: We conducted a retrospective cohort analysis of the UNOS database and identified all pediatric recipients of kidney transplantation between 2000 and 2018. We compared donor and recipient characteristics, including cause of ESRD, among patients who lost their graft due to BKVN or other causes, and those with functioning allograft. Kaplan–Meier curve and Cox regression analysis were performed to evaluate the risk factors. Results: A total of 66 patients (0.47%) suffered graft failure from BKVN. Older age, male gender, HLA mismatch, and rejection at 1 year were significantly associated with BKVN graft failure, compared to recipients with functioning allograft. In comparison with graft loss due to other causes, male gender, higher HLA mismatch, rejection in 1st year and tacrolimus use at discharge were significantly associated with BKVN graft loss. Recipients who received mycophenolate at time of discharge were at reduced risk for BKVN graft failure. Compared to graft failure from other causes, BKVN graft failure had shorter death censored graft survival [ P  = .001]. ESRD due to urologic causes and Alport syndrome had higher rate of BKVN graft failure. Conclusion: Incidence of graft loss from BKVN in the pediatric population was 10.2 per 10 000 patient‐years in this study. BKVN is associated with early allograft failure in the pediatric population, compared to other causes of graft loss. Male gender, HLA mismatch, rejection in 1st year, and urological cause of ESRD are risk factors for graft failure from BKVN in children.